Challenges and Benefits of Using Wiki-based Collaborative Writing in EFL Classes - L.B. Yibreh; B.B. Haile (Moscow State University of Psychology and Education, 2023)
The challenges and benefits of wiki that students encounter during the process of implementing wiki in EFL writing classes is the focus of the research that need to be investigated. The emphasis of the research is to look at the benefits and challenges that university students faced during the implementation of wiki-based collaborative writing at Addis Ababa Science and Technology University. The participants were enrolled in a noncredit essay-writing course that was linked with the wiki platform. Questionnaires and focus group discussion were used to collect data. All students completed questionnaires and focus group discussion to investigate the benefits of using wiki. Descriptive statistics such as frequency and mean were used to analyze the quantitative data. To analyze the data, themes about benefits of using wiki were used. Students faced both psychological and functional challenges. Students discussed that they collaborated during the process of using wiki and their writing skills was improved. Finally, English as a Foreign Language writing skills teachers should carefully train students on how to use social media like a wiki in their curricula.